Determinants of Remittances : Evidence From tonga - Lin, Huidan (IMF Working Papers; Working Paper ;, 2011)
This paper analyzes the determinants of remittances to Tonga. The results indicate that macroeconomic conditions in remitting countries and exchange rate fluctuations influence remittances. In particular, remittances growth falls when the Tongan currency appreciates, but increases with higher real GDP growth and lower unemployment in remitting countries. The analysis also finds that the influence of these determinants varies with the recipients of remittances, with remittances to non-profit organizations being more sensitive to an appreciation of the Tongan currency and the interest rate differential between Tonga and remitting countries than remittances to households. However, the analysis does not find evidence of "ADutch Disease" in Tonga, as the real exchange rate does not appear to be affected by remittances.